Papuan Women Community Empowerment through Coconut Derivative Product Training in Kampung Payum, Merauke - Adiatma, Tini; Prasetya, Muhammad Novan; Yuliatun, Tutik; Majid, Ilham; Arafa, Guntur (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Papuan Indigenous People in Payum Village, Merauke, who are mostly fishermen, face economic challenges due to the impact of climate change which has the potential to reduce fish catches. On the other hand, women in this village have not been actively involved in potential economic activities. The strategy to overcome these challenges is to conduct training in making coconut derivative products, such as body butter, solid soap, body scrub, and lip balm. This training aims to empower the community, especially women, by improving their skills in utilizing the abundant potential of coconuts to create value-added business opportunities. The results of the training showed success in improving the understanding and skills of the participants. The participants, under the guidance of expert speakers from Makassar, succeeded in producing various coconut derivative products according to standards. In addition, this training also facilitated the formation of women's business groups as a strategic step in community empowerment in Payum Village. With further assistance, this activity is expected to be able to create economic independence for the community and become a model of empowerment based on local potential to deal with the impacts of climate change.